PERCEPTIONS OF TEENAGERS ABOUT SEX EDUCATION IN â€œDUA GARIS BIRUâ€ MOVIE - Pertiwi, Dian Ayu; Fajrie, Mahfudlah; Arianto, Dwi Agung Nugroho (An-Nida : Jurnal Komunikasi Islam, 2024)
The Dua Garis Biru Film is a 2019 Indonesian teen drama film directed by Gina S. Noer. This film received various responses from the public when the trailer was shown, because it raised the theme of teenage pregnancy and provided an understanding of sex education in adolescent life. The purpose of this study was to determine the perception of Jepara teenagers about sex education in the Dua Garis Biru film. This type of research is qualitative with a socio-psychological approach, the research subjects are teenagers from Jepara Regency, taken through purposive sampling technique. The results showed that the Dua Garis Biru film caused two perceptions, namely positive and negative regarding the message of sex education in it. Positive perception states that sex education is important and good for educating teenagers to be more vigilant in socializing in order to avoid premarital sex and prioritize education. Meanwhile, the negative perception is that not all teenage viewers can understand the message of sex education contained in the Dua Garis Biru film